A nurse‐coordinated integrated care model to support decision‐making and self‐care in patients with atrial fibrillation: A study protocol. (27th August 2019) - Li, Polly W. C.; Yu, Doris. S. F.; Yan, Bryan B. Y.
Abstract: Aim: This study aims to evaluate the effects of a nurse‐coordinated, empowerment‐based integrated care model on self‐care behaviours and psychosocial outcomes in patients with atrial fibrillation and to explore how this intervention affects patients' self‐care behaviours and quality of life. Design: This mixed‐methods study comprises a randomized controlled trial and an exploratory qualitative study. Methods: A total of 392 community‐dwelling patients aged ≥65 years with a confirmed diagnosis of atrial fibrillation, a high stroke risk and no oral anticoagulants treatment will be recruited from the medical outpatient clinics of a university‐affiliated hospital. The patients will be randomly allocated to intervention or control groups, which will receive treatment via the nurse‐coordinated integrated care model or standard care, respectively. We hypothesize that compared with patients receiving standard care, atrial fibrillation patients exposed to the nurse‐coordinated care model will be more likely to achieve compatible patient and physician decisions regarding the use of oral anticoagulants, better changes in medication adherence, anxiety, depression and health‐related quality of life after the intervention. A subsample of 30 participants in the intervention group will also participate in a qualitative interview to provide their views and perceptions about the intervention. The ethical approval has obtained on 5 July 2018. This study is supported by a grant from the Research Grants Council of the Hong Kong Special Administrative Region on 29 June 2018. Discussion: This study will uniquely adopt an empowerment‐based approach to equip patients as active agents in atrial fibrillation management through a nurse‐coordinated integrated care model that comprehensively addresses their needs. Impact: Patients with atrial fibrillation are currently receiving inadequate guideline‐recommended care. This study will address this important evidence‐practice gap by optimizing oral anticoagulant prescription and therapeutic effects and promotes effective patient self‐care, so as to achieve worldwide reductions in atrial fibrillation‐related morbidity, mortality, and healthcare burdens. Clinical Trial Registration: This study has been registered at ClinicalTrials.gov (NCT03924739). Abstract : 目的: 本研究旨在评估护士协作、基于赋权的综合护理模式对心房纤颤患者自我护理行为和心理社会结果的影响, 并探讨这种干预将如何影响患者的自我护理行为和生活质量。 设计: 本混合方法研究包括随机对照实验和探索性质的定性研究。 方法: 将从附属大学医院的门诊招募共392名年龄≥65岁的确诊有心房纤颤、高中风风险且没有口服抗凝药物的社区患者。患者将被随机分配到干预组或对照组, 分别通过护士协调综合护理模式或标准护理接受治疗。我们假设相比于病人接受标准护理, 房颤患者接受护士协调综合护理模式将更容易实现患者和医生关于使用抗凝血剂决定兼容。更好的药物治疗依从性的变化, 焦虑、抑郁和健康相关的干预后生活质量。干预组的30名参与者也将参加一个定性访谈, 以提供他们对干预的看法和感知。这项研究于2018年7月5日获得道德审批, 于2018年6月29日获得香港大学特别行政区研究资助局的资助。 讨论: 本研究将采用一种独特的基于授权的方法, 使用护士协调综合护理模式, 使患者成为房颤管理中的积极因素, 从而全面满足他们的需求。 影响: 房颤患者目前接受的指导手册推荐的治疗还不充分。本研究将通过优化口服抗凝药物处方和治疗效果来解决这一重要的证据‐实践差距, 并促进有效的患者自我护理, 从而实现在全世界范围内降低心房纤颤相关疾病的发病率、死亡率和医疗负担。 临床试验注册: 这一研究在Clinical Trials.gov网站注册(NCT03924739)。